STRATEGI PUBLIC RELATION DALAM MENINGKATKAN BRAND IMAGE ASTON BATAM - RAHMAYANI, IKA PUTRI RAHMAYANI; CINDOSWARI, AGENG RARA (SCIENTIA JOURNAL, 2022)
The tourism sector in Indonesia has very good levels and contributions, especially on the island of Batam, of course this will also increase the potential for businesses related to the tourism sector, one of which is hospitality. Batam is an area that is more dominantly visited by tourists compared to other regions in the Riau Archipelago, this is because public places such as ports, airports, malls and other tourist attractions are in Batam City. This makes the competition in the hotel business world in Batam City even higher. Of course, having a good Brand Image will increase the superiority of competing hotels by implementing several public relations strategies. This research took place at the Aston Batam Hotel & Residence with exploratory qualitative research techniques through observation, interviews, and literature review. The results of the research show that the public relations strategy in improving the Brand Image of Aston Batam Hotel & Residence is to carry out publications and SWOT analysis by making sales calls or visits to several companies or agencies to find out about the internal environment of Strengths and Weaknesses as well as external Opportunities and Threats faced by the world effort.